(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The study of the proverb and sayings through linguocultural approach is efficient today. The linguocultural approach to the parmeological units helps reveal the peculiar features of the definite culture. Being the product of the folk, the parmeological units as proverbs and saying illustrate the life, traditions, history of the nation, the mind and the world outlook of people, thus,giving the impetius to forming the parmeological world picture.